Back to the future: A sovereign debt standstill mechanism IMF Article VIII, Section 2 (b) - Daniel Munevar; Grygoriy Pustovit (Leibniz Institute for Financial Research SAFE, 2020)
This article provides a proposal to use IMF Article VIII, Section 2 (b) to establish a binding mechanism on private creditors for a sovereign debt standstill. The proposal builds on the original idea by Whitney Deveboise (1984). Using arguments brought forward by confidential IMF staff papers (1988, 1996) and the IMF General Counsel (1988), this paper shows how an authoritative interpretation of Article VIII, Section 2 (b) can provide protection from litigation to countries at risk of debt distress. The envisaged mechanism presents several advantages over recent proposals for a binding standstill mechanism, such as the International Developing Country Debt Authority (IDCDA) by UNCTAD and a Central Credit Facility (CFF) by the Bolton Committee. First, this approach would not require the creation of new intergovernmental mechanisms or facilities. Second, the activation of the standstill mechanism can be set in motion by any IMF member country and does not require a modification of its Articles of Agreement. Third, debtor countries acting in good faith under an IMF program would be protected from aggressive litigation strategies from holdout creditors in numerous jurisdictions, including the US and the UK. Fourth, courts in key jurisdictions would avoid becoming overburdened by a cascade of sovereign debt litigation covering creditors and debtors across the globe. Fifth, private creditors would receive uniform treatment and ensure intercreditor equality. Sixth and last, the mechanism would provide additional safeguards to protect emergency multilateral financing provided to tackle Covid-19.
Keywords: 330; sovereign debt standstill; sovereign debt restructuring; sovereign debt litigation; holdout litigation; vulture creditors